VD_FINDINFO Jug / 2020 / 262 vom 13. Februar 2020 - VD Tribunal cantonal (2020)
ACCÈS INDU À UN SYSTÈME INFORMATIQUE, FIXATION DE LA PEINE, INTERNEMENTDROIT PÉNAL | 143bis CP, 19 CP, 47 CP, 49 CP, 56 CP, 64 CP